MULTILINGUALISM IN THE LINGUISTIC LANDSCAPE AT GRANADA ISLAMIC HERITAGE SCHOOL AND IMPACT ON THE SCHOOL’S LANGUAGE ENVIRONMENT - al wafi, abdullah; Setiadi, Syamsi; Failasuf, Chakam (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
ABSTRACT This study analyzes the multilingual practice of Granada Islamic Heritage School from the point of view of linguistic landscape. It utilizes a qualitative research approach. Its primary focus is probing the existence and dissemination of three languages (English, Indonesian, and Arabic) in the public realms in the school such as information boards, motivational signs, and visual instructional aids.Data were gathered through participatory observation and visual documentation of language signs in the school environment. A description of language code use was constructed through analysis to determine the representation of religious, national, and global identity in the school.Results indicate that the simultaneous presence of three languages creates a dynamic language environment that can support both formal language acquisition and informal social communication. Arabic supports religious identity, while English and Indonesian support global communicative competence and local identity. Most importantly, the integration of the linguistic landscape becomes an extra value to students, linguistic capacity making their reading, writing, and speaking skills robust in all three languages and developing multilingual awareness and positive attitudes towards linguistic diversity.Thus, the language environment of Granada Islamic Heritage School functions as a rich pedagogical resource, establishing a rich, multicultural learning culture that significantly facilitates students’ language learning.